An Operational System for Smoothing Batch-Type Production - O'Malley, Richard L.; Elmaghraby, Salah E.; Jeske, John W. (Management Science, 1966)
This paper describes a production smoothing system which combines several known scheduling tools into an operational unit. The input to the system is forecasted customer demand; the outputs are the required production levels, size of labor force, planned overtime and expected inventories of classes and individual end products. Because of varying demand, economic manufacturing quantities are calculated by the method of dynamic programming following Wagner and Whitin. The manufacturing progress function is used to convert units into labor requirements. Finally, the operating schedule is derived by a linear programming formulation which balances payroll costs, the costs of labor fluctuations, and inventory charges. This system has been in operation for several months.